Applying dialogic pedagogy in science education learning environment in Early childhood education (ECE) in China - Shi, Wencheng (2023)
Dialogic pedagogy can foster the formation of learning community in science education learning environment. At the same time, dialogue pedagogy and science education both focus on process development. However, the majority of studies have used quantitative research methods to quantify the science education learning environment. Consequently, few process-based studies have been conducted in the science education learning environment. Furthermore, the existing quantitative studies usually focus on the primary and secondary age groups, rather than early childhood education(ECE). To address this gap, this study, applies dialogic pedagogy in science education learning environment in ECE in China and further investigates its impact from social, physical and psychological perspectives.